2017
DOI: 10.4269/ajtmh.16-0557
|View full text |Cite
|
Sign up to set email alerts
|

Management of Advanced Hepatic Alveolar Echinococcosis: Report of 42 Cases

Abstract: Abstract. Radical resection is the first choice for hepatic alveolar echinococcosis (HAE). However, many patients with advanced HAE have no chance to be treated with curative resection owing to the long clinical latency. This study aimed to evaluate the necessity of aggressive operations, like palliative resection and orthotopic liver transplantation (OLT), in the management of advanced HAE. A retrospective study analyzed 42 patients with advanced HAE treated with palliative resection (N = 15), palliative nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…The survival rate of patients undergoing R0 resection with clear margins was 100% after a 300-month follow-up [34]. Nevertheless, the risk of mortality and postoperative complications including hemorrhage or sepsis is substantial [34,35]. As would have been the case in our patient, radical resection is generally difficult due to infiltrative disease or multiplicity of cysts involving different liver segments [36].…”
Section: Discussionmentioning
confidence: 57%
“…The survival rate of patients undergoing R0 resection with clear margins was 100% after a 300-month follow-up [34]. Nevertheless, the risk of mortality and postoperative complications including hemorrhage or sepsis is substantial [34,35]. As would have been the case in our patient, radical resection is generally difficult due to infiltrative disease or multiplicity of cysts involving different liver segments [36].…”
Section: Discussionmentioning
confidence: 57%
“…Besides, achieving 2 cm resection margin for every single lesion is not possible in most advanced cases as recommended [3,4,28,30]. For excessive vascular in ltrated lesion or with severe comorbidities, only liver transplantation or ex vivo liver resection and autotransplantation could be selected from the perspective surgical treatment [11,[31][32][33][34][35][36][37][38][39][40]. Our data indicated that, different lesion types had different immune cell in ltrated belt.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, achieving 2 cm resection margin for every single lesion is not possible in most advanced cases as recommended [3,4,28,30]. For excessive vascular infiltrated lesion or with severe comorbidities, only liver transplantation or ex vivo liver resection and autotransplantation could be selected from the perspective surgical treatment [11,[31][32][33][34][35][36][37][38][39][40]. Our data indicated that, different lesion types had different immune cell infiltrated belt.…”
Section: Discussionmentioning
confidence: 99%